Reirradiation: Standards, challenges, and patient‐focused strategies across tumor types - Arnaud Beddok; Jonas Willmann; Anna Embring; Ane L. Appelt; Panagiotis Balermpas; Kevin Chua; J. Isabelle Choi; Bernice Simone Elger; Dorota Gabrys; Peter Hoskin; Maximilian Niyazi; David Pasquier; et al. (CA: A Cancer Journal for Clinicians, 2025)
Abstract Reirradiation (reRT), defined as administering a course of radiation therapy to a specific area previously irradiated, is an evolving treatment strategy for locoregionally recurrent cancer that offers significant potential and poses inherent challenges. Advances in such techniques as intensity‐modulated and stereotactic body radiation therapy have improved precision, making reRT a viable option for complex scenarios previously deemed high‐risk. Nevertheless, reRT remains associated with substantial risks—including life‐threatening side effects, functional impairments, and psychosocial effects—which must be carefully balanced against the patient's overall health and the likelihood of achieving cancer control or palliation. Patient selection is essential to optimize outcomes while mitigating risks. Decisions should account for tumor characteristics at the time of primary diagnosis and recurrence, elapsed time since prior treatment, the possibility of delivering meaningful doses to the tumor, and the cumulative irradiation tolerance of normal tissues. Advanced imaging modalities, such as functional magnetic resonance imaging and fluorine‐18–labeled fluorodeoxyglucose–positron emission tomography, are important for distinguishing recurrences from treatment‐induced changes, refining treatment targets, and minimizing exposure to healthy tissue. Combined treatment with systemic regimens—targeted therapies and immunotherapy in particular—offers promising opportunities but requires coordination to manage side effects. Standardized guidelines, such as those from the European Society of Therapeutic Radiology and Oncology‐European Society for Research and Treatment of Cancer, are essential for improving the consistency of reporting, guiding clinical decision making, and fostering patient‐centered care. Multidisciplinary collaboration and ongoing research, particularly through clinical trials, are central to fully exploiting reRT strategies. In addition, the development of innovative techniques, such as proton therapy, would likely enable safer treatments. These efforts aim to improve the therapeutic balance of reRT, enhancing outcomes and quality of life.